PRMT7: A Pivotal Arginine Methyltransferase in Stem Cells and Development - Bingyuan Wang; Mingrui Zhang; Zhiguo Liu; Yulian Mu; Kui Li (Stem Cells International)
Protein arginine methylation is a posttranslational modification catalyzed by protein arginine methyltransferases (PRMTs), which play critical roles in many biological processes. To date, nine PRMT family members, namely, PRMT1, 2, 3, 4, 5, 6, 7, 8, and 9, have been identified in mammals. Among them, PRMT7 is a type III PRMT that can only catalyze the formation of monomethylarginine and plays pivotal roles in several kinds of stem cells. It has been reported that PRMT7 is closely associated with embryonic stem cells, induced pluripotent stem cells, muscle stem cells, and human cancer stem cells. PRMT7 deficiency or mutation led to severe developmental delay in mice and humans, which is possibly due to its crucial functions in stem cells. Here, we surveyed and summarized the studies on PRMT7 in stem cells and development in mice and humans and herein provide a discussion of the underlying molecular mechanisms. Furthermore, we also discuss the roles of PRMT7 in cancer, adipogenesis, male reproduction, cellular stress, and cellular senescence, as well as the future perspectives of PRMT7-related studies. Overall, PRMT7 mediates the proliferation and differentiation of stem cells. Deficiency or mutation of PRMT7 causes developmental delay, including defects in skeletal muscle, bone, adipose tissues, neuron, and male reproduction. A better understanding of the roles of PRMT7 in stem cells and development as well as the underlying mechanisms will provide information for the development of strategies for in-depth research of PRMT7 and stem cells as well as their applications in life sciences and medicine.